Happy birthday to you! - Depken, Kristen L; Aikins, Dave; Penguin Random House; Random House Children's Books; Viacom International (New York Random House, 2018)
The twin genies and their friends prepare for a very special birthday party
At head of title: Shimmer and Shine
English Stories
Preschool-Kindergarten
Keywords: Birthdays -- Juvenile fiction; Parties -- Juvenile fiction; Sisters -- Juvenile fiction; Birthday parties -- Fiction; Genies -- Fiction; Sisters -- Fiction; Twins -- Fiction; Birthdays; JUVENILE FICTION -- Girls & Women; JUVENILE FICTION -- Media Tie-In; JUVENILE FICTION -- Social Themes -- Friendship; Parties; Sisters; Fiction; Juvenile works; Readers (Publications); Readers (Publications)